Spring report - Bierman, Dicket al (1978)
Field notes titled "spring report," submitted by Dick Bierman, May 23, 1978. The opening paragraph suggests that these sightings were made in North-West Iowa and were done in cooperation with Marion M. Brewer, who submitted a separate report. An annotation next to a note mentioning the sighting of a White-eyed Vireo at Cherokee reads "extends margins of range." This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed